PERTUMBUHAN DAN HASIL TANAMAN JAGUNG LOKAL VARIETAS MOTOROKIKI PADA BEBERAPA KELAS LERENG DAN DOSIS PUPUK NPK DI PAYU, GORONTALO - Andri Husain; Nurdin Baderan; Sutrisno Hadi Purnomo (Jurnal Tanah dan Sumberdaya Lahan, 2022)
Maize local of Motorokiki variety is a Gorontalo germplasm which is cultivated more dominantly on sloping land with low productivity. This study was aimed to determine the growth and yield of local maize on several slope classes and doses of NPK fertilizer, and their combination on the growth and yield of local maize in Payu, Gorontalo. This study used a split-plot design with the main plot of slope class and sub-plots of NPK fertilizer dosage. The main plot of the slope class consisted of flat slopes (0-8%), wavy (8-15%), hilly (15-35%) and mountainous (>35%), while sub-plots with NPK fertilizer dosage consisted of 0 kg ha-1, 50 kg ha-1, 100 kg ha-1, 150 kg ha-1 and 200 kg ha-1. The parameters measured included plant height, leave numbers, male and female flowering age, cob length, and weight of corn kernels. Data were analyzed by the Duncan Multiple Range Test (DMRT) at 5% level. The results showed that maize growth was significantly affected by slope class and NPK fertilizer dosage with the best combination of wavy slope and 50 kg ha-1 fertilizer dosage. In maize yield, only maize seed weight was significantly affected by slope class, while in NPK fertilization only on male and female flowering age with the best combination of flat slope class and 100 kg ha-1 fertilizer dosage.